An evaluation approach for modules developed from design structure matrix. (19th April 2021) - Li, Ying; Ying, Baosheng; Rong, Zhijun; Dan, Binbin; Hu, Conglin; Xiang, Feng
The main characteristics of its components and their interaction are represented in products architecture. A modular architecture can enhance the whole design cycle of a product. The idea of module identification is to minimise interactions between modules and maximise component interconnection within each module. Clustering DSM is a popular analysis technique for modularity. To assess the clustering efficiency, a new index of Cce is tendered to deal with a numerical DSM, as well as a binary DSM. A case study of a motorcycle engine of 17 parts is analysed using the proposed assessment to get a better clustering result, which validates the feasibility of the evaluation approach.